Relatório final de estágio curricular em Prática Veterinária, realizado junto ao Setor de Clínica Médica de Pequenos Animais da UNESP FCAV (Jaboticabal - SP) e à Clínica Veterinária Feline (Ribeirão Preto - SP): Caso de Interesse: Esporotricose em paciente felino no município de Ribeirão Preto/SP - Chagas, Maria Eduarda Moraes das [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
O presente trabalho tem por objetivo descrever e discutir as atividades desenvolvidas durante o período de Estágio Curricular em Prática Veterinária, sendo este um elemento obrigatório da grade curricular do curso de Medicina Veterinária da Faculdade de Ciências Agrárias e Veterinárias (FCAV) - UNESP, Câmpus de Jaboticabal para obtenção do título de Médico(a) Veterinário(a).

The present work aims to describe and discuss the activities developed during the period of the Curricular Internship in Veterinary Practice, which is a mandatory element of the curriculum grade of the Veterinary Medicine course at the Faculty of Agricultural and Veterinary Sciences (FCAV) - UNESP, Jaboticabal Campus to obtain the title of Veterinary Doctor.
Final report of the curricular internship in Veterinary Practice, carried out at the Small Animal Medical Clinic Department of UNESP FCAV (Jaboticabal - SP) and the Feline Veterinary Clinic (Ribeirão Preto - SP): Case of Interest: Sporotrichosis in a feline patient in the city of Ribeirão Preto/SP.
Keywords: Esporotricose; Saúde Pública Veterinária; Micoses